If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(x + -4) = 2(x + -4) Reorder the terms: 3(-4 + x) = 2(x + -4) (-4 * 3 + x * 3) = 2(x + -4) (-12 + 3x) = 2(x + -4) Reorder the terms: -12 + 3x = 2(-4 + x) -12 + 3x = (-4 * 2 + x * 2) -12 + 3x = (-8 + 2x) Solving -12 + 3x = -8 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -12 + 3x + -2x = -8 + 2x + -2x Combine like terms: 3x + -2x = 1x -12 + 1x = -8 + 2x + -2x Combine like terms: 2x + -2x = 0 -12 + 1x = -8 + 0 -12 + 1x = -8 Add '12' to each side of the equation. -12 + 12 + 1x = -8 + 12 Combine like terms: -12 + 12 = 0 0 + 1x = -8 + 12 1x = -8 + 12 Combine like terms: -8 + 12 = 4 1x = 4 Divide each side by '1'. x = 4 Simplifying x = 4
| (x+3)(x+2)= | | 3x-3=3x-6 | | 2x+x-4=2x-4-2 | | 2x+x-4=2x-6 | | x*3.2+0.8=x*5.7-0.4 | | 3x-4=2x-6-2 | | x^2-5x+11=0 | | x^2+16x-5=0 | | -16x^2+64x+50=0 | | Y=35-5x | | 2(-x)-(-3+x)=2x+8 | | 1.25x+2.45=0.3 | | 9x-7(x-1)= | | 3x^2+12x+14=0 | | 15x^2-12x=0 | | (9a^3+3a^2)+(5a^3+6a^2)= | | x^2+9x-13=0 | | (-3x)(2)=x+2+3x | | 5a+2c=3280 | | 10x-1=x | | 13-7x=2x+58 | | x=0.5 | | 5z-7=13-3z | | s(s-6)=-8 | | 16x=(30x-15)-20 | | 6n^2+2n-140=0 | | b^2+6b-7=0 | | 4c^2+9xy-9y^2= | | -3v+10=40 | | 7p^2-4p=0 | | 16x^2-96x-100=0 | | 3k^2-22k+24=0 |